2010
DOI: 10.1177/0194599810390893
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Surface Dehydration on Mucosal Wave Amplitude and Frequency in Excised Canine Larynges

Abstract: Objective Evaluate the effect of vocal fold surface dehydration on mucosal wave amplitude and frequency. Study Design Controlled test-retest. Setting Larynges were mounted on an excised larynx phonation system and attached to a pseudolung in a triple-walled sound-attenuated room that eliminated background noise and maintained a stabilized room temperature and humidity level. Subjects and Methods High-speed video was recorded for eight excised canine larynges during exposure to dehumidified air at 20 cm H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 26 publications
0
31
1
1
Order By: Relevance
“…Although previous research has revealed that the fundamental frequency significantly decreased in dehydrated larynges, 15 there was no significant difference in this study. Dehydration was able to cause muscle contraction, which could result in a larger glottal gap.…”
Section: Discussioncontrasting
confidence: 91%
“…Although previous research has revealed that the fundamental frequency significantly decreased in dehydrated larynges, 15 there was no significant difference in this study. Dehydration was able to cause muscle contraction, which could result in a larger glottal gap.…”
Section: Discussioncontrasting
confidence: 91%
“…These deleterious effects of desiccated air on precise phonation have also been confirmed in a series of ex vivo studies with excised canine and ovine larynges (31)(32)(33). This confirmation suggests plainly that the sensitivity of speakers' vocal cords to desiccated air is genotypically and phenotypically normal and operative across all human populations.…”
Section: Significancementioning
confidence: 61%
“…It stiffens the cover of vocal folds and increases the viscosity of mucosa, 36 which, in turn, changes the mucosal wave by decreasing its amplitude and frequency. 37,38 As a result, the phonation threshold pressure increases. [39][40][41][42] Some voice ergonomic risk factors, like working posture and emotions, are related to the speaker.…”
Section: Introductionmentioning
confidence: 99%